Learning forms - Pérez, Éloïsa (Base Diseño e Innovación, 2016)
Motivated by the desire to clarify the links between pedagogy, graphic design and typography, Learning Forms is presented as a global research project whose objective is to develop the dialog between these disciplines, encouraging the sharing of work experiences and the collaborations between designers and schools. It was initiated in 2013 by Éloïsa Pérez, in the context of her Masters Degree in the National Higher School of Decorative Arts (Ensad), with a focus on the study and observation of the joints that graphic systems offer and the devices for knowledge transmission.This project is part of a laboratory of educational tools conception that claim its materiality and testify the attention given to the objects that are part of a learning process. These tools are part of a methodology both theoretical and practical, since they verify the assumptions raised by the problems that guide the project.